Optimalisasi Potensi Herbal Tradisional Minyak Balur Karo sebagai Produk Ekonomi Kreatif Berbasis Budaya di Dusun V Mandai Angin Desa Aji Baho Kecamatan Biru Biru Kabupaten Deli Serdang - Ginting, Evfy Septriani (INSTITUT KESEHATAN DELI HUSADA, 2025)
The production of traditional herbal oil represents a significant local economic potential that can be further developed through the application of appropriate technology and community empowerment programs. However, limitations in equipment, lack of hygiene awareness, and the absence of modern marketing strategies remain the main obstacles in improving product quality and competitiveness. To address these challenges, the Community Service Team conducted a program titled “Training and Practice of Tawar Latih Herbal Oil Production as an Effort to Enhance Skills and Economic Independence of the Ajibaho Village Community, Biru-Biru District, Deli Serdang Regency.” This activity involved two community groups, namely Mawar Merah Group and Mawar Putih Group, with a total of 20 participants, supported by 20 members of the Student Executive Board (BEM) of Deli Husada Institute of Health as field assistants. The training was conducted in two stages: theoretical sessions and hands-on practice (learning by doing). Participants learned about the selection of high-quality ingredients, temperature control during heating, the use of the Oil Mixing Machine, filtering and hygienic packaging processes, and digital marketing strategies. Evaluation was carried out through observation and interviews to assess participants’ improvement in technical and managerial abilities. The results showed an improvement of more than 85% in participants’ capabilities related to processing, quality control, and small business management. Furthermore, the Mawar Putih Group, consisting of local youth, successfully promoted their products through Shopee, TikTok, YouTube, and other social media platforms, expanding their market reach. The program also increased production capacity up to 100 liters per day, reduced material waste by about 20%, and produced herbal oil that was clearer, more aromatic, and longer-lasting. Overall, this program effectively enhanced community skills in hygienic herbal oil production, fostered local entrepreneurship, and strengthened collaboration between the community, the village government, and BEM of Deli Husada Institute of Health. This collaborative model is expected to serve as a sustainable community service framework for developing local products based on regional potential and appropriate technological innovation.